2013
DOI: 10.1016/j.jmb.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Multiple C-Terminal Tails within a Single E. coli SSB Homotetramer Coordinate DNA Replication and Repair

Abstract: E. coli single strand DNA binding protein (SSB) plays essential roles in DNA replication, recombination and repair. SSB functions as a homotetramer with each subunit possessing a DNA binding domain (OB-fold) and an intrinsically disordered C-terminus, of which the last nine amino acids provide the site for interaction with at least a dozen other proteins that function in DNA metabolism. To examine how many C-termini are needed for SSB function we engineered covalently linked forms of SSB that possess only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 89 publications
8
65
0
Order By: Relevance
“…Since removal of the CTD moved the peak, this confirms that it is exclusively the CTDs (residues 107-171) that contribute to this flexibility in solution. This result is in line with previous observations that the SSB CTD has flexible properties (as predicted through difficulties with protein crystallisation and secondary structure predictions) and the observation that the NTD forms a rigid tetramer with no major flexibility [3,6]. Addition of dT35 or dT70 at one-fold molar excess over tetramer does not change the shape of the curve suggesting that despite compaction, the CTD remains somewhat mobile.…”
Section: Distance Distribution Functions -P(r) Plots -(Figsupporting
confidence: 91%
“…Since removal of the CTD moved the peak, this confirms that it is exclusively the CTDs (residues 107-171) that contribute to this flexibility in solution. This result is in line with previous observations that the SSB CTD has flexible properties (as predicted through difficulties with protein crystallisation and secondary structure predictions) and the observation that the NTD forms a rigid tetramer with no major flexibility [3,6]. Addition of dT35 or dT70 at one-fold molar excess over tetramer does not change the shape of the curve suggesting that despite compaction, the CTD remains somewhat mobile.…”
Section: Distance Distribution Functions -P(r) Plots -(Figsupporting
confidence: 91%
“…We also found that DnaN levels were increased, suggesting that dnaN is damage inducible. We suggest that the basal recOR-independent RecA localization we observe in ssb⌬35 cells is caused by elevated RecA levels in vivo, which may be caused or exacerbated by a decrease in the ability of ssb⌬35 to bind ssDNA (62).…”
Section: Resultsmentioning
confidence: 79%
“…The EcoSSB contains a nine-amino acid sequence (C-terminal tail) that binds to more than a dozen different proteins that it recruits to their sites of function in DNA replication, repair, and recombination (1,21), and it regulates the ssDNA binding affinity and cooperativity between binding sites (22). In human mtSSB, this C-terminal tail is completely missing (5), which raises the questions of whether mtSSB may show distinct ssDNA binding modes and whether the kinetic and thermodynamic basis for formation of protein-DNA complexes is different from that for EcoSSB.…”
mentioning
confidence: 99%